ADABIY MAKONNING KOMPOZITSION YAXLITLIGI - Allanazarova, F.K. (SCIENCE and SOCIETY, 2025)
This article explains the compositional integrity of the artistic chronotope, the way the text emerges, the uniqueness of the writer’s concept, and the modernity of the mythological interpretation as a result of the combination of many components, such as perception and imagination.